Antonius Andrias Reis Tanesi Program Studi Keuangan Dan Perbankan,Akademi Keuagan Dan Perbankan Effata Kup - Antonius Andrias Reis Tanesi; Jose Rizaldi Manafe (STIKes Ibnu Sina Ajibarang, 2023)
The development of the potential of MSMEs in Indonesia cannot be separated from banking support in distributing financing to MSME players. The role of BPR in developing community businesses, especially MSMEs, is to participate in providing financing to the community to develop their businesses. The aim of this research is to determine the effect of providing micro credit on the development of MSME customers of BPR TLM Kas Naikoten and to determine the difference in customer income before and after receiving credit. The research methodology used is a quantitative approach. The sample used was BPR TLM Kas Naikoten Micro Credit Customers from 2021 to 2022, totaling 79 respondents. The data analysis used in this research is simple linear regression analysis and comparison tests, with the help of SPSS version 24. The results of the research conducted show that the provision of microcredit has a significant effect on the development of MSME customers of PT. BPR TLM Cash Naikoten. The development of the Customer's business occurs in increasing business capital, increasing sales turnover, increasing income, expanding the business and increasing the workforce. And there is a significant difference in the income level of PT customers. BPR TLM Kas Naikoten before and after receiving microcredit. The average income of customers after receiving BPR TLM Kas Naikoten micro credit has increased, where the average income before receiving micro credit is IDR 2,912,063.29 and after receiving micro credit is IDR 3,589,506.33.